2019
DOI: 10.1093/mnras/stz1181
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic OB[A] Stars with TESS: probing their Evolutionary and Rotational properties (MOBSTER) – I. First-light observations of known magnetic B and A stars

Abstract: In this paper we introduce the MOBSTER collaboration and lay out its scientific goals. We present first results based on the analysis of nineteen previously known magnetic O, B and A stars observed in 2-minute cadence in sectors 1 and 2 of the Transiting Exoplanet Survey Satellite (TESS ) mission. We derive precise rotational periods from the newly obtained light curves and compare them to previously published values. We also discuss the overall photometric phenomenology of the known magnetic massive and inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 137 publications
(189 reference statements)
0
24
0
Order By: Relevance
“…No rotation period is reported in the literature for this star with Mathys et al (2020b) classifying the star as a super slowly rotating Ap (ssrAp) star, although the longitudinal field measurements reported in the catalogue by Bagnulo et al (2015) do show some indication of variability on the time scale of a few years. No sign of rotation variability was found in any of the published analyses of the TESS data (Cunha et al 2019;David-Uraz et al 2019;Mathys et al 2020b).…”
Section: Tic 139191168mentioning
confidence: 87%
“…No rotation period is reported in the literature for this star with Mathys et al (2020b) classifying the star as a super slowly rotating Ap (ssrAp) star, although the longitudinal field measurements reported in the catalogue by Bagnulo et al (2015) do show some indication of variability on the time scale of a few years. No sign of rotation variability was found in any of the published analyses of the TESS data (Cunha et al 2019;David-Uraz et al 2019;Mathys et al 2020b).…”
Section: Tic 139191168mentioning
confidence: 87%
“…This would be a new important step into the recent domain of magneto-asteroseismology, but such observational detections have not been made yet. The new TESS samples of pulsating OB stars are promising in this respect (David-Uraz et al 2019;Neiner et al, in prep.). To progress even further on magneto-seismic diagnostics, a non-perturbative treatment of the magnetic field would be needed to be able to consider (i) a magnetic field that is not confined inside the star, and (ii) stronger fields such as those of Ap stars.…”
Section: Discussionmentioning
confidence: 99%
“…Their light curves (detrended following the procedure described by Bowman et al 2018), which show similarities with those of known magnetic stars (e.g. David-Uraz et al 2019), and the associated Lomb-Scargle periodograms are shown in Fig. 1.…”
Section: Target Selectionmentioning
confidence: 95%